<span><span>b[1]=3
q=-2
b[2]=b[1]q
b[2]=3*(-2)=-6
b[3]=b[2]*q
b[3]=-6*(-2)=12
b[4]=b[3]*q=12*(-2)=-24
b[5]=b[4]q=-24*(-2)=48
S[5]=b[1]+b[2]+b[3]+b[4]+b[5]
<span>S[5]=3+(-6)+12+(-24)+48=33</span>
или по формуле суммы
S=b[1]*(q^n-1)/(q-1)
<span>S=3*((-2)^5-1)/(-2-1)=33</span>
</span>
</span>
Ответ:
Пошаговое объяснение:
8х - (х - 4) = 8х - х + 4 = 7х + 4
7 * (-7) + 4 = - 45
761 см = 7 м 61 см = 7 м 6 дм 1 см
604 см = 6м 4 см = 6 м 0 дм 1 см
<span>Значение выражения не зависит от переменных
</span>
<span>
</span>
(2.2/100)(7/1000)=15.4/100000=1.54*10^-4